2013
DOI: 10.1097/opx.0b013e318278153c
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Refraction and Retinal Contour in Stable and Progressive Myopia

Abstract: Stable and progressing myopes of matched age, axial length, and central refraction showed significantly different characteristics in their peripheral retinal shape and astigmatic components of tangential and sagittal power errors. The present findings may help explain the mechanisms that regulate ocular growth in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 34 publications
3
45
3
5
Order By: Relevance
“…Investigations into myopia control over the previous decade have generated theories to explain why Ortho-K slows axial length increases in myopic children [48][49][50]. Most have centered on the effect of the optical changes to the peripheral refractive profile created by Ortho-K.…”
Section: How Ortho-k Slows Myopic Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into myopia control over the previous decade have generated theories to explain why Ortho-K slows axial length increases in myopic children [48][49][50]. Most have centered on the effect of the optical changes to the peripheral refractive profile created by Ortho-K.…”
Section: How Ortho-k Slows Myopic Progressionmentioning
confidence: 99%
“…But, peripheral to the macular area, while spectacle and contact lens correction creates relative peripheral hyperopia, Ortho-K creates relative peripheral myopia [51][52][53][54][55][56]. This relative peripheral myopic defocus inhibits the signaling for the eye to elongate [50].…”
Section: How Ortho-k Slows Myopic Progressionmentioning
confidence: 99%
“…The relative positions of the sagittal and tangential foci might be crucial to understand the mechanisms that guide the elongation of the eye. [17][18][19] Indeed, a study conducted in rhesus monkeys suggested that the emmetropization mechanism might by guided by the astigmatic defocus instead of the spherical equivalent defocus. The results suggested that the growth mechanism might be guided by the image plane that contains the maximum effective contrast and stimulus orientation.…”
Section: Introductionmentioning
confidence: 97%
“…Retinal shape can be estimated by indirect optical methods that are based on peripheral refraction [11][12][13], partial coherence interferometry [14][15][16][17][18][19][20][21][22][23][24] and optical coherence tomography [25,26]. However such methods rely on assumptions concerning shape and refractive index distribution through the lens and other structures within the eye, in order to convert optical path lengths into geometrical dimensions.…”
Section: Introductionmentioning
confidence: 99%